Training Management for Patient Education in Critical Care Areas at a Central General Hospital in Manado, Indonesia - Mordekhai L Laihad; Joulanda A M Rawis; Rolles N. Palilingan; Joseph Philip Kambey (International Journal of Information Technology and Education, 2025)
Patient and family education is a cornerstone of quality healthcare, particularly in critical care areas where clinical uncertainty, high-risk decisions, and emotional distress converge. Despite its recognized importance, patient education in intensive care settings often remains inconsistent due to time pressure, heavy workloads, communication barriers, and limited standardized tools. This qualitative case study analyzes how training management can improve patient education practices in a critical care environment at a central general hospital in Manado, Indonesia. The study examines (1) training planning and needs assessment, (2) training implementation strategies, (3) training evaluation, and (4) contextual factors influencing success. Data were collected through in-depth interviews, FGDs, observation, and document review, and analyzed using an interactive approach supported by triangulation. Findings indicate that patient education quality was initially suboptimal, reflected in frequent refusal of medical procedures (approximately 50 cases per month), high family anxiety (around 80%), and inconsistent use of educational media. Key factors shaping patient education included nurses’ workload and time constraints, cultural and literacy barriers among families, variability in communication competence, and uneven availability and enforcement of SOPs and supporting media. A Training Needs Analysis (TNA) identified gaps across six key competency domains and informed the development of ten training modules. Training was delivered through simulation, role play, and bedside coaching, improving staff compliance with patient education SOPs from 38% to 70%. Evaluation using the Kirkpatrick and CIPP models suggested that training was relevant and impactful, although some outcome targets remained unmet. Recommendations include digitalizing education media, strengthening SOP implementation, embedding training into performance appraisal systems, and expanding training across units.